Legal Protection for Farmer Groups in Subsidized Fertilizer Pricing: A Case Study in Kualuh Hilir, North Sumatra - Roby Andreansyah Putra; Mhd Yadi Harahap (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
Discrepancies between subsidized fertilizer prices and the government-mandated Maximum Retail Price (HET) continue to undermine agricultural productivity and policy effectiveness in Indonesia. This study examines the legal protection afforded to farmer groups affected by such price deviations, focusing on a case study in Kualuh Hilir Subdistrict, North Labuhanbatu Regency. Employing a socio-legal approach, the research combines normative legal analysis - reviewing Law No. 19 of 2013 on the Protection and Empowerment of Farmers, Minister of Agriculture Regulation No. 10 of 2022 as amended by Regulation No. 1 of 2024, and relevant constitutional provisions - with empirical fieldwork, including semi-structured interviews, direct observations, and document analysis. Findings reveal that extended distribution chains, weak regulatory oversight, delayed subsidy disbursements, and low legal literacy among farmers are the primary factors driving price discrepancies, resulting in farmers paying significantly above the regulated HET. These findings underscore a persistent gap between Indonesia’s legal frameworks and their practical implementation, leaving smallholders vulnerable to exploitation. This study contributes to socio-legal scholarship on agrarian justice by providing micro-level evidence of how systemic weaknesses in subsidy governance undermine farmers’ legal protections. Policy recommendations include strengthening distribution regulations, establishing accessible grievance mechanisms, and improving farmer legal literacy to enhance subsidy program effectiveness and ensure constitutional guarantees of agrarian justice are realized.